2017
DOI: 10.3390/lubricants5040048
|View full text |Cite
|
Sign up to set email alerts
|

Field Tests on Hydrodynamic and Hybrid Operation of a Bidirectional Thrust Bearing of a Pump-Turbine

Abstract: Abstract:In vertical shaft pump turbines operating in pumped storage power plants an important role is played by a thrust bearing. Due to the bidirectional character of operation, thrust bearing tilting pads have to be supported symmetrically, which is known to be unfavourable from the point of view of their performance. Large thrust bearings have to be carefully designed so as to minimise excessive thermo-elastic pad deformations. The research into fluid film thrust bearings has been quite extensive over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…HS bearings are often combined with HD bearings to reduce wear during the start and stop phase [15], compensate for misalignment, and are frequently mounted on the tilting support of the pad [16]. The HS lubrication regime increases the thickness of the film and improves circulation and cooling [17], thus improving its performance. This is one of the main reasons why HS lubrication is used as bearings on high-precision machines.…”
Section: Introductionmentioning
confidence: 99%
“…HS bearings are often combined with HD bearings to reduce wear during the start and stop phase [15], compensate for misalignment, and are frequently mounted on the tilting support of the pad [16]. The HS lubrication regime increases the thickness of the film and improves circulation and cooling [17], thus improving its performance. This is one of the main reasons why HS lubrication is used as bearings on high-precision machines.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments are crucial to CFD model validation, especially in cases where exact analytical approaches cannot be used. Wasilczuk et al [33] concluded that the presence of HS pockets in hydrodynamic bearings reduces the temperature change and pressure peaks, leading to higher stability of operation. The drawback of the presence of the pocket is the larger friction losses due to the cooler oil.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments are crucial to CFD model validation, especially in cases where exact analytical approaches cannot be used. Wasilczuk et al [33] concluded that the presence of HS pockets in hydrodynamic bearings reduces the temperature change and pressure peaks, leading to higher reliability of the hybrid bearing, but the drawback of the presence of the pocket is the larger friction losses due to the cooler oil. Wodtke et al [34] carried out experimental validation for theoretical calculations and predictions of large hydrodynamic thrust bearings and emphasized the necessity of experimental validation of numerical simulations, which are simplified and thus do not represent the real geometry and other influential effects.…”
Section: Introductionmentioning
confidence: 99%